Hubungan Faktor Terapi Dengan Tingkat Kepatuhan Pnggunaan Obat Pasien Systemic Lupus Erythematosus (SLE) Di Rumah Sakit Umum Daerah Arifin Achmad Provinsi Riau - Husnawati - Husnawati; Novia Sinata; Maya Sari (LPPM Universitas Abdurrab, 2026)
Systemic Lupus Erythematosus (SLE) is a chronic autoimmune disease that requires long-term therapy to control symptoms and prevent organ damage. This study aims to determine the relationship between therapy factors and the level of compliance in SLE patients using the chi-square test with a sample of 64 respondents selected by purposive sampling. The research instrument, the MGLS questionnaire, was used to assess patient compliance. The results showed that the duration of treatment and drug side effects had a significant relationship (P<0.05) with the level of compliance, while the complexity of treatment did not have a significant relationship with the level of compliance (P>0.05). This study indicates that drug side effects are one of the important factors influencing the compliance of SLE patients with therapy